A new lab-made screen-printed electrode system based on reduced graphene oxide-subphthalocyanine functionalized with ferrocene for electrochemical detection of acetaminophen - Alahmad, Haala; Gul, Elif Yildiz; Aksoy, Burcu Topaloglu; Biryan, Fatih; Koran, Kenan; Ecik, Esra Tanriverdi; Bas, Salih Zeki (Elsevier, 2025)
Acetaminophen (Ac) is a pharmaceutically active ingredient widely used in the treatment of pain and fever. However, an acute oral overdose of more than 12 g of Ac is considered a toxic dose and poses a high risk of liver damage. This study presents the development of a new laboratory-made screen-printed electrode modified with reduced graphene oxide (rGO)-subphthalocyanine-functionalized with ferrocene (SubPc-Fc) to detect Ac. Initially, subphthalocyanine (SubPc) was synthesized using a known method from the literature and was then functionalized with ferrocene (Fc). Subsequently, this functionalized compound was combined with rGO to form a composite structure (rGO-SubPc-Fc). A laboratory-made screen-printing electrode (LabSPE) was successfully created by using carbon and silver conductive inks applied to a polycarbonate substrate through the screenprinting process. Then, the surface of LabSPE was modified with rGO-SubPc-Fc composite and made ready for the electrochemical determination of Ac. The electrochemical results revealed that the rGO-SubPc-Fc composite exhibited a remarkable sensing behavior towards the oxidation of Ac with a working range from 0.05 mu M to 200 mu M, and a detection limit of 0.01 mu M. The selectivity of the proposed sensor (rGO-SubPc-Fc/LabSPE) for Ac detection in the presence of possible interfering compounds such as uric acid, epinephrine, ascorbic acid, dopamine, and some ions was also examined. The practical suitability of rGO-SubPc-Fc/LabSPE in real sample analysis was tested on two different types of human drug samples and appreciable recovery results were obtained in the range of 102.02-103.94 %. In drug sample analysis, the proposed method was compared with the spectrophotometric method, and satisfactory results were achieved.
Keywords: Subphthalocyanine; Ferrocene; Lab-made SPE; Electrochemical sensor; Acetaminophen